The Impact of Financial Literacy on Gen Z’s Investment Interest in Indonesia’s Sharia Capital Market - An'im Falahuddin Achmad; Alisep Sandi Prayoga; Wahyu Widodo (Prodi Ekonomi Syariah Universitas Pangeran Diponegoro Nganjuk, 2025)
Indonesia experienced a 300% surge in Gen Z investors entering the capital market during the pandemic, yet financial literacy remains critically low at 47.2% (OJK 2023). This study investigates how financial literacy influences Gen Z's investment interest, examining risk perception as a moderator and religiosity as a mediator. A mixed-method approach combined quantitative surveys of 500 Gen Z investors with qualitative netnography of TikTok/Instagram investment content. Key results indicate financial literacy significantly predicts investment interest (β = 0.68), but social media content exerts four times stronger initial impact on engagement decisions. Religiosity actively mediates sharia investment intent by strengthening ethical alignment, while risk perception moderates literacy effects by reducing speculative behavior. These findings necessitate redesigning digital financial education through algorithmic delivery systems and collaborations with social media influencers. Specifically, implementing TikTok/Instagram content adaptation with sharia-integrating modules can bridge literacy gaps while resonating with Gen Z's digital-native behaviors.